2009
DOI: 10.1038/nm.2011
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia can both mediate and suppress Hedgehog pathway–dependent tumorigenesis

Abstract: Primary cilia are present on most mammalian cells and are implicated in transducing Hedgehog (Hh) signals during development; however, the prevalence of cilia on human tumors remains unclear, and the role of cilia in cancer has not been examined. Here we show that human basal cell carcinomas (BCCs) are frequently ciliated, and we test the role of cilia in BCC by conditionally deleting Kif3a (encoding kinesin family member 3A) or Ift88 (encoding intraflagellar transport protein 88), genes required for ciliogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
419
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(455 citation statements)
references
References 38 publications
31
419
2
3
Order By: Relevance
“…Current data indicate that localization of SMO to cilium is not sufficient to activate hedgehog signaling (Rohatgi et al, 2009;Wilson et al, 2009a). Using Kif3a tissue-specific gene knockout, recent studies revealed dual roles of cilium for hedgehog signaling carcinogenesis in mouse models Wong et al, 2009). Although Kif3a is required for SMO-mediated tumor formation, deletion of Kif3a accelerates Gli2-mediated carcinogenesis.…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…Current data indicate that localization of SMO to cilium is not sufficient to activate hedgehog signaling (Rohatgi et al, 2009;Wilson et al, 2009a). Using Kif3a tissue-specific gene knockout, recent studies revealed dual roles of cilium for hedgehog signaling carcinogenesis in mouse models Wong et al, 2009). Although Kif3a is required for SMO-mediated tumor formation, deletion of Kif3a accelerates Gli2-mediated carcinogenesis.…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…More specifically, a subset of individuals with BCC harbor a mutant activated form of Smo that is constitutively localized to cilia. To investigate the role of cilia in oncogenesis, mouse models of BCC and medublastomas were generated by targeting constitutively active Smo to skin cells and cerebellar granule neuron precursors, respectively (Han et al, 2009;Wong et al, 2009). Strikingly, when Kif3a or Ift88 were genetically ablated in the altered cell types, tumor formation was inhibited.…”
Section: Today's Relevancementioning
confidence: 99%
“…Cette découverte suggère que la ségrégation différentielle des centrioles en fonction de leur âge, et donc l'apparition asynchrone des cils, pourraient influencer le destin cellulaire des deux cellules filles et leur capacité à se différencier au sein d'un tissu. Un nombre important de mutations dans des gènes codant pour des molécules impliquées dans la ciliogenèse a été identifié dans des maladies génétiques, de nombreux syndromes (MeckelGruber), des maladies du rein (polykystose rénale) [42] et des cancers [43][44][45]. De plus, dans certains cas, l'identité des cellules souches dépend de leur positionnement.…”
Section: L'importance Du Centrosome Dans La Ciliogenèse Et Les Maladiunclassified